2021
DOI: 10.1017/s002221512100267x
|View full text |Cite
|
Sign up to set email alerts
|

No lasting impact of Covid-19 on the auditory system: a prospective cohort study

Abstract: Objective: Whereas otologic complications are considered as early symptoms of SARS-CoV-2, it is unknown how long they last and whether the virus leaves any hearing disorders postrecovery.Methods: Thirty-one mild or moderate confirmed cases with Covid-19 and 26 age-matched control peers (21-50yr) were included in this prospective cohort study. Patients were questioned about their otologic symptoms, and their hearing status was assessed during one-month postdiagnosis.Results: Patients showed a significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Hearing loss and tinnitus were the next two most often reported complaints, both of which recovered during the second phase. Our findings corroborated the finding of Hassani et al (23), who reported that the audiovestibular symptoms resolved over time. Therefore, several audiovestibular complications reported during COVID-19 infection may be temporary.…”
supporting
confidence: 93%
“…Hearing loss and tinnitus were the next two most often reported complaints, both of which recovered during the second phase. Our findings corroborated the finding of Hassani et al (23), who reported that the audiovestibular symptoms resolved over time. Therefore, several audiovestibular complications reported during COVID-19 infection may be temporary.…”
supporting
confidence: 93%
“…In current study, there was no significant difference between the study and control groups as regards low repetition & high repetition rates ABR parameters (table 6). This finding is consistent with a study conducted by Hassani et al (22) who stated that there was no significant difference between the study and control groups as regards ABR parameters at high and low repetition rates.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have highlighted the effect of COVID-19 infection on the functioning of the auditory system, but the results so far have not been consistent [2,[4][5][6][7][8][9]. The present study aims to assess the auditory system functioning in individuals post-COVID-19 infection and to compare the results from individuals who have not been infected.…”
Section: Introductionmentioning
confidence: 93%
“…Its manifestations are changing with time, and infected individuals show a gamut of symptoms ranging from fever, mild to moderate respiratory illness, fatigue, and gastrointestinal complaints[2,16]. Individuals with COVID-19 can have longterm complications, including lung damage, neurological ing function tests[5,9,[17][18][19][20][21][22] while others have shown, in patients who have recovered from mild-to-moderate degrees of infection, no significant difference before and after COVID-19 infection[6][7][8]23]. In 2020 Mustafa reported significantly reduced high-frequency pure-tone thresholds and reduced otoacoustic emission (OAE) amplitude in…”
mentioning
confidence: 99%